2016
DOI: 10.4172/2161-1122.1000370
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hypertension in Endodontic Clinics: A Pilot Study

Abstract: Background: Hypertension is one of the leading causes of death worldwide, and a major risk factor for heart diseases and strokes. A lot of undiagnosed or uncontrolled hypertensive patients seek dental treatment in regular basis. However, neither doctors nor patients are doing enough to fight and diagnose this silent killer disease. This study investigated the prevalence of undiagnosed or uncontrolled hypertensive patients who visited our endodontic clinic for dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
1
0
1
Order By: Relevance
“…Hypertension was the most frequent systemic disorder both before and during the pandemic. This result was similar to that of Bogari et al, who reported that hypertension was the most common systemic disorder (63.7%) among their endodontic patients (15). As one in every three people worldwide is expected to develop hypertension in their lifetime (15), the high frequency of this disorder in our study is not unexpected.…”
Section: Original Articlesupporting
confidence: 92%
See 1 more Smart Citation
“…Hypertension was the most frequent systemic disorder both before and during the pandemic. This result was similar to that of Bogari et al, who reported that hypertension was the most common systemic disorder (63.7%) among their endodontic patients (15). As one in every three people worldwide is expected to develop hypertension in their lifetime (15), the high frequency of this disorder in our study is not unexpected.…”
Section: Original Articlesupporting
confidence: 92%
“…This result was similar to that of Bogari et al, who reported that hypertension was the most common systemic disorder (63.7%) among their endodontic patients (15). As one in every three people worldwide is expected to develop hypertension in their lifetime (15), the high frequency of this disorder in our study is not unexpected. Clinicians have a duty to evaluate risk factors for this systemic disease as part of health care, especially during the pandemic.…”
Section: Original Articlesupporting
confidence: 92%
“…It’s interesting to note that, in line with previous research, among our group, which had a mean age of 44.58 years, similar participants were referred for hypertension, and a sizable number were ignorant of their illness. Among patients at screened endodontic clinics, Bogari & Bakalka (2016) discovered a significant prevalence of hypertension (63.7%), with more than half being unaware of their illness. According to Saeedi et al (2019) , type 2 diabetes is a very frequent condition that affects 9.0% of women and 9.6% of men worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…4 A hipertensão, considerada uma das principais causas de morte no mundo, é um exemplo, uma vez que a ausência de sintomas suscita o atendimento de pacientes descompensados ou não diagnosticados. 7 Por conseguinte, o cirurgião-dentista muitas vezes é o responsável pela abordagem inicial da hipertensão através da aferição de pressão arterial pré-operatória, avaliação de risco e encaminhamento médico. 8 Essa perspectiva torna-se um problema diante da negligência por parte de alguns profissionais, que não fazem o condicionamento pré-operatório envolvendo aferição de pressão arterial; estudos demonstraram que 55% dos profissionais realizam a aferição previamente.…”
Section: Introductionunclassified